A Study of Certain Geometric Properties and Hardy Spaces of the Normalized Miller-Ross Function - Abubakr, Muhammad; Raza, Mohsan; Alenazi, Abdulaziz; Mehrez, Khaled (Mathematics (Basel), 2025)
The main objective of this research is to investigate specific sufficiency criteria for the strongly starlikeness, strongly convexity, starlikeness, convexity and pre-starlikeness of the normalized Miller-Ross function. Furthermore, we establish sufficient conditions under which the normalized Miller-Ross function belongs to Hardy spaces and the class-bounded analytic functions. Some of the various results which are derived in this paper are presumably new and their significance is illustrated through several interesting examples.